High-flow vs conventional oxygen therapies for acute cardiogenic pulmonary edema following hip fractures and surgery in elderly patients - Ci, Caizhe; Tong, Xiao; Tai, Weiyan; Geng, Xiaoyong; Han, Yu; Zhang, Xiaojun (Frontiers in Oncology, 2025)
PurposeThis prospective, randomized controlled study aimed to compare the effects of high-flow oxygen therapy and conventional oxygen therapy in the treatment of acute cardiogenic pulmonary edema following hip fractures and surgery in elderly patients.MethodsFrom February 2018 to October 2023, 124 patients diagnosed with acute cardiogenic pulmonary edema following hip fractures and surgery were randomly assigned to the high-flow oxygen therapy group (n=62) or conventional oxygen therapy group (n=65). Partial pressure of oxygen (PO2) and blood oxygen saturation (SPO2) were assessed 60 minutes after the treatments. A P value <0.05 was considered statistically significant.ResultsThere were significant differences in PO2 (66.2 ± 3.3 mmHg vs 62.1 ± 3.4 mmHg, P<0.05) and SPO2 (97.8 ± 2.1 mmHg vs 94.2 ± 1.7 mmHg, P<0.05) between the groups.ConclusionIn the treatment of elderly patients with ACPE following hip fractures and surgery, high-flow oxygen therapy may be performed to improve ventilation when acute cardiogenic pulmonary edema does not significantly improve within 15 minutes of conventional oxygen therapy.